Diagnosis of α-thalassemia-1 southeast Asian type deletion and fetal gender by single-tube multiplex real-time PCR - Sarinee Srithep (2018)
Background: The combination of an x-linked hematologic disorder with a heterozygous α-thalassemia-1 Southeast Asian (SEA) type deletion might lead to severe anemia in male infants. This study is to develop a simple and cost-effective single tube multiplex real-time PCR for the diagnosis of α-thalassemia-1 SEA type deletion and detect fetal gender. Methods: Multiplex real-time polymerase chain reaction (PCR) for the detection of α-thalassemia-1 SEA type deletion gene, wild type α-globin gene, and sex-determining region Y (SRY) gene was validated by analysis of 95 cord blood samples (60 normal individuals, 28 heterozygous of α-thalassemia-1 SEA type deletion and 7 Bart's hydrops fetalis). The change in threshold cycle (ΔCT) was analyzed by subtracting the CT-mutant from CT-wild type. Results: Mean ΔCT values were significantly different among these three groups, and a SRY gene determination was 100% in concordance with fetal genders. Furthermore, analysis of fetal gender did not affect the ΔCT of α-thalassemia-1 SEA detection. Conclusions: Combined α-thalassemia-1 SEA type detection and fetal gender determination in a single-tube multiplex real-time PCR is an alternative assay for a conventional method for the diagnosis of α-thalassemia-1 SEA deletion and fetal gender.